The Role of Financial Planning and Management for The Welfare of The People Through The Mosque (Case Study of Several Mosques in Medan City) - Azka Rayyani; Khairunnisa Abd Samad; Hendra Harmain (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to Analyse the role of financial planning and management for the welfare of the people through the mosque. The research method used is a case study by conducting interviews with mosque administrators, mosque financial managers and several worshipers. The results showed that the implementation of good financial plans and management in the mosque was able to increase the income of the mosque and worshipers, manage expenses effectively and provide benefits to worshipers and the surrounding community.